It takes two to pantomime: Communication meets motor cognition - Lisa Finkel; Katharina Hogrefe; Scott H. Frey; Georg Goldenberg; Jennifer Randerath (NeuroImage: Clinical, 2018)
For over a century, pantomime of tool use has been employed to diagnose limb apraxia, a disorder of motor cognition primarily induced by left brain damage. While research consistently implicates damage to a left fronto-temporo-parietal network in limb apraxia, findings are inconsistent regarding the impact of damage to anterior versus posterior nodes within this network on pantomime. Complicating matters is the fact that tool use pantomime can be affected and evaluated at multiple levels. For instance, the production of tool use gestures requires the consideration of semantic characteristics (e.g. how to communicate the action intention) as well as motor features (e.g. forming grip and movement). Together, these factors may contribute substantially to apparent discrepancies in previously reported findings regarding neural correlates of tool use pantomime.In the current study, 67 stroke patients with unilateral left-brain damage performed a classic pantomime task. In order to analyze different error characteristics, we evaluated the proper use of grip and movement for each pantomime. For certain objects, healthy subjects may use body parts as representative for the object, e.g. use of the fingers to indicate scissors blades. To specify the pathological use of body parts as the object (BPO) we only assessed pantomime items that were not prone to this response in healthy participants. We performed modern voxel-based lesion analyses on MRI or CT data to determine associations between brain injury and the frequency of the specific types of pantomime errors.Our results support a model in which anterior and posterior nodes of the left fronto-temporo-parietal network contribute differentially to pantomime of tool use. More precisely, damage in the inferior frontal cortex reaching to the temporal pole is associated with an increased frequency of BPO errors, whereas damage to the inferior parietal lobe is predominantly linked to an increased frequency of movement and/or grip errors. Our work suggests that the validity of attempts to specify the neural correlates of limb apraxia based on tool use pantomime depends on differentiating the specific types of errors committed. We conclude that successful tool use pantomime involves dissociable functions with communicative aspects represented in more anterior (rather ventral) regions and motor-cognitive aspects in more posterior (rather dorsal) nodes of a left fronto-temporo-parietal network. Keywords: Pantomime, BPO, Motor cognition, Communication, Dual routes, Neural correlates